Avaliação da evolução das comorbidades da obesidade mórbida e sua relação com a massa corpórea após cinco anos da derivação gástrica em Y de Roux com anel de contenção - Laurino Neto, Rafael Melillo [UNIFESP] (2011)
BACKGROUND: Roux-en-Y gastric bypass (RYGB) is considered an effective therapy for weight loss although weight regain may be observed in a long-term follow-up. Obesity-related comorbidities are also well treated by RYGB due to weight loss and intestinal hormone changes. Few studies reported long-term status of comorbidities especially if weight regain is present. This study aims to analyze: (1) the resolution of obesity-related comorbidities after RYGB in a long-term follow-up and (2) its relationship to weight regain. METHODS: 140 patients (mean age 41, 18 male, mean body mass index (BMI) before operation 52 (range 39-82) kg/m2, mean BMI at nadir weight 29 (range 18-46) kg/m2, mean BMI at last follow-up 33 (range 19-49) kg/m2 were followed-up after RYGB for morbid obesity for at least 5 years (mean follow-up 90, range 60-155 months). Diabetes, cardiovascular disease, arterial hypertension, dyslipidemia, sleep apnea, arthropathy, and infertility were present when submitted to surgery in 26 (18%), 14 (10%), 88 (62%), 18 (13%), 83 (59%), 90 (64%), 9 (16%) patients; and in 6 (4%), 8 (5%), 38 (27%), 6 (4%), 45 (32%), 75 (53%), 7 (12%) patients at the Nadir weight, respectively. RESULTS: BMI was significantly different in the 3 periods. Comorbidities resolution was sustained in a long-term follow-up for diabetes, hypertension, cardiopathy and infertility. Comorbidities status was direct related to the % of weight loss for all comorbidities except infertility. CONCLUSION: Our results show that comorbidities remission after RYGB is sustained in the majority of patients in a long-term follow-up. Weight regain is linked to worse results for all comorbidities except infertility.